2019
DOI: 10.1111/tbj.13344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of primary tumor resection on overall survival in patients with stage IV breast cancer

Abstract: We aimed to evaluate the effect of primary tumor resection on overall survival in stage IV breast cancer patients. In total, 284 breast cancer patients presenting with breast cancer at stage IV at initial diagnosis, between 2001 and 2014, were enrolled in the study. Patients were divided into two groups based on surgical resection of the primary tumor. Overall survival (OS) between the two groups was analyzed. Patients in the surgery group (n = 92) had smaller tumors than those in the no‐surgery group (n = 192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…LRT can consist of surgery alone, RT alone, or both. Several retrospective series have reported an association between LRT and improved survival in patients with stage IV breast cancer at the time of diagnosis [ 9 , 10 , 11 , 12 , 13 , 14 ]. A meta-analysis including 28,693 patients found that surgical excision of the primary breast lesion improved the three-year survival from 22% to 40% ( p < 0.01) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…LRT can consist of surgery alone, RT alone, or both. Several retrospective series have reported an association between LRT and improved survival in patients with stage IV breast cancer at the time of diagnosis [ 9 , 10 , 11 , 12 , 13 , 14 ]. A meta-analysis including 28,693 patients found that surgical excision of the primary breast lesion improved the three-year survival from 22% to 40% ( p < 0.01) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a Korean study shows that, curiously, in a 5-year overall survival rate of 49% and 29.8% for surgery and no surgery, respectively, regarding tumor subtype, the luminal B had significantly better overall survival with surgery (OS rate = 63.9%, p =0.03) [15]. The reason for these results is not clear, but is hopeful considering the current prognosis for these patients and is something to be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…As with all retrospective reviews, there was a possible patient selection bias contributing to the better results in the patients after surgery [ 9 ]. Patients with better conditions and less risk were reported to be more likely to receive surgical interventions [ 7 ]. Therefore, the actual benefit from surgery for stage IV breast cancer should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…As to the United States, approximately 5% of women with newly diagnosed breast cancer were reported to present with stage IV at diagnosis [ 7 ]. The proportion of stage IV breast cancer was even higher in the Asian population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%